Growth optimalization of bileh fish seeds (Rasbora sp.) through different feeding frequencies - Nurfaizah, Nurfaizah; Islama, Dini; Rahmayanti, Fitria; Febrina, Citra Dina (Universitas Malikussaleh, 2024)
Bileh fish is a type of freshwater fish that is sought after by the people of Aceh because it has a delicious taste and is quite tasty. Bileh fish is a local fish species that has the potential to be developed as an aquaculture commodity and its population must be preserved from overfishing. The aim of this research was to determine the effect of different feeding frequencies on the growth of bileh fish fry (Rasbora sp.). This research used a non-factorial completely randomized design (CRD) method consisting of 4 treatments and 3 replications each, namely the frequency of feeding 1 time/day (P1), feeding 2 times/day (P2), feeding 3 times/day day (P3) and feeding 4 times/day (P4). The feed given is commercial feed PF 500 with 39% protein. The parameters observed included survival rate, length growth, weight growth, daily growth rate, feed efficiency and water quality. The results showed that different feeding frequencies had no significant effect on survival rate, absolute length and daily growth rate of bileh fish (Rasbora sp.). However, it has a real effect on weight growth and feed efficiency. The best feeding frequency to optimize the weight growth of bileh fish (Rasbora sp.) is in the P3 treatment with a frequency of 3 times/day.Keywords: Feed Efficiency; Feeding Frequency; Growth; Rasbora